THE EFFECT OF FERMENTED PAPAYA (Carica papaya L.) LEAF EXTRACT THROUGH DRINKING WATER ON THE ORGANOLEPTIC QUALITY OF KUB CHICKEN MEAT - N. K. A. D., CAHYANI; SRIYANI, N. L. P.; E., PUSPANI (Majalah Ilmiah Peternakan; Vol 27 No 2 (2024): Vol. 27 No. 2 (2024), 2024)
This study aims to determine the effect of administering fermented papaya (Carica papaya L.) leaf extract thro- ugh drinking water on the organoleptic quality of KUB chicken meat. The design used was a completely randomized design (CRD) with 4 treatments and 4 replications, each replication consisting of 3 KUB chickens aged 10 days. The- se treatments include P0 (KUB chickens given drinking water without the addition of fermented papaya leaf extract (Carica papaya L.) as a control), P1 (KUB chickens given drinking water with the addition of 2% fermented papaya leaf extract (Carica papaya L.) P2 (KUB chickens given drinking water with the addition of 4% fermented papaya (Carica papaya L.) leaf extract), and P3 (KUB chickens given drinking water with the addition of 6% fermented papaya (Carica papaya L.) leaf extract). The variables observed were the organoleptic quality of the meat (color, texture, aroma, taste and overall acceptability). The results of the study showed that administering fermented papa- ya leaf extract through drinking water could improve the organoleptic quality of KUB chicken meat which includes color, texture, aroma, taste and overall acceptance.